(untitled) (Baghdad Science Journal, 2015)
In this study, hexadecyltrimethylammonium bromide (HDMAB) - bentonite was synthesized by placing alkylammonium cation onto bentonite. Adsorption of textile dye such as direct Yellow 50 on natural bentonite and HDMAB -bentonite was investigated. The effects of pH, contact time,dosage clay and temperature were investigated experimentally .The Langmuir and Freundlish isotherms equations were applied to the data and values of parameters of these isotherm equations were evaluated. The study indicated that using 0.2 g of HDMAB (hexadecyltrimethylammonium bromide) lead to increase the percentage removal(R%) from 78% for pure bentonite to 99 %. The optimum pH value for the adsorption experiments was found to be pH=3 and therefore all the experiments were carried out at this pH value. The pseudo-second-order kinetic model agrees very well with the experimental results.Different thermodynamic parameters such as Gibb’s free energy, enthalpy and entropy of the on-going adsorption process have also been evaluated. The thermodynamic analyses of the dye adsorption on organoclay indicated that the system was endothermic in nature .